I'm your man: How suppliers gain strategic status in buying companies. Issue 2 (June 2016) - Andersen, Poul Houman; Ellegaard, Chris; Kragh, Hanne
Abstract: Selecting suppliers and deciding which suppliers to develop strategic relationships with is important for buying organisations. However, little is known about how strategic suppliers become recognised as such in the first place. We provide a detailed and explorative case study of supplier categorisation processes among actors in buying organisations. The social process of categorising and evaluating supplier inputs has been referred to as status creation. We map sensegiving processes and how they influence supplier status development using a longitudinal case study approach. Highlights: Suppliers' strategic status emerges over time as internal stakeholders recognise and understand the suppliers' abilities and how this may match with existing projects. Key internal promoters and the supplier's own efforts in creating recognition are crucial in this process. Shared understandings in buying companies depend on key events which further trust and strengthens the status of the supplier.